Chronic Obstructive Pulmonary Disease and Metabolic Syndrome: A Maltese Study on Biomarkers and Clinical Implications - Gauci J; Gauci Pullicino S; Caruana E; Petroni Magri V; Formosa MM; Fenech AG; Fava S; Montefort S; Fsadni P (Diabetes, Metabolic Syndrome and Obesity)
Jonathan Gauci,1,2 Stephanie Gauci Pullicino,1,2 Emma Caruana,2 Vanessa Petroni Magri,3,4 Melissa Marie Formosa,4,5 Anthony G Fenech,3,4 Stephen Fava,1,2 Stephen Montefort,2 Peter Fsadni1,2 1Department of Medicine, Mater Dei Hospital, Msida, Malta; 2Department of Medicine, Faculty of Medicine and Surgery, University of Malta, Msida, Malta; 3Department of Clinical Pharmacology and Therapeutics, Faculty of Medicine and Surgery, University of Malta, Msida, Malta; 4Centre for Molecular Medicine and Biobanking, University of Malta, Msida, Malta; 5Department of Applied Biomedical Science, Faculty of Health Sciences, University of Malta, Msida, MaltaCorrespondence: Jonathan Gauci, Department of Medicine, Mater Dei Hospital, Triq Dun Karm, Msida, MSD2090, Malta, Email jonathan.gauci@gov.mtPurpose: Chronic Obstructive Pulmonary Disease (COPD) and Metabolic Syndrome (MetS) are both characterized by inflammation and appear to be linked. The study aims to characterize COPD in Maltese individuals with diabetes and MetS for the first time. The research project also aims to identify biomarkers that are significantly associated with COPD endpoints in the study population having both COPD and MetS.Patients and Methods: The study was carried out at Mater Dei Hospital, which is Malta’s main general hospital and is government managed. Research subjects were recruited from the Diabetes Clinic. A respiratory questionnaire was administered, followed by the Six-Minute Walk Test (6MWT), Fractional Exhaled Nitric Oxide (FeNO) testing, spirometry and phlebotomy. The American Heart Association (AHA) and National Heart, Lung, and Blood Institute (NHLBI) criteria were used to diagnose MetS. A post-bronchodilator FEV1/FVC ratio of less than 0.7 was necessary to diagnose COPD, as recommended by Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines.Results: The study group consisted of 24 subjects diagnosed with both MetS and COPD. The group showed heterogenous results with a mean St George’s Respiratory Questionnaire for COPD total score of 41.7, mean distance on 6MWT of 359m, mean FeNO of 12.2ppb, and mean Forced Expiratory Volume in 1 second of 64.6%. While 62.5% had a modified Medical Research Council score of ≥ 2, 95.8% had a COPD Assessment Test score of ≥ 10. One-fourth of the group were at risk for clinical depression, and 20.8% showed severe fatigue. Blood lymphocyte count, ferritin, triglycerides and glucose were significantly associated with multiple respiratory parameters in diabetic MetS subjects with COPD.Conclusion: The local diabetic MetS study population with COPD is heterogenous, with high levels of depression and fatigue. The emergence of biomarkers in this population has clinical and therapeutic implications.Keywords: biomarkers, depression, fatigue